Bioinformatics and molecular dynamics simulation study of L1 stalk non-canonical rRNA elements: kink-turns, loops, and tetraloops - Krepl, Miroslav; Réblová, Kamila; Koča, Jaroslav; Sponer, Jiří (The journal of physical chemistry. B, 2013)
The L1 stalk is a prominent mobile element of the large ribosomal subunit. We explore the structure and dynamics of its non-canonical rRNA elements, which include two kink-turns, an internal loop, and a tetraloop. We use bioinformatics to identify the L1 stalk RNA conservation patterns and carry out over 11.5 μs of MD simulations for a set of systems ranging from isolated RNA building blocks up to complexes of L1 stalk rRNA with the L1 protein and tRNA fragment. We show that the L1 stalk tetraloop has an unusual GNNA or UNNG conservation pattern deviating from major GNRA and YNMG RNA tetraloop families. We suggest that this deviation is related to a highly conserved tertiary contact within the L1 stalk. The available X-ray structures contain only UCCG tetraloops which in addition differ in orientation (anti vs syn) of the guanine. Our analysis suggests that the anti orientation might be a mis-refinement, although even the anti interaction would be compatible with the sequence pattern and observed tertiary interaction. Alternatively, the anti conformation may be a real substate whose population could be pH-dependent, since the guanine syn orientation requires protonation of cytosine in the tertiary contact. In absence of structural data, we use molecular modeling to explore the GCCA tetraloop that is dominant in bacteria and suggest that the GCCA tetraloop is structurally similar to the YNMG tetraloop. Kink-turn Kt-77 is unusual due to its 11-nucleotide bulge. The simulations indicate that the long bulge is a stalk-specific eight-nucleotide insertion into consensual kink-turn only subtly modifying its structural dynamics. We discuss a possible evolutionary role of helix H78 and a mechanism of L1 stalk interaction with tRNA. We also assess the simulation methodology. The simulations provide a good description of the studied systems with the latest bsc0χOL3 force field showing improved performance. Still, even bsc0χOL3 is unable to fully stabilize an essential sugar-edge H-bond between the bulge and non-canonical stem of the kink-turn. Inclusion of Mg(2+) ions may deteriorate the simulations. On the other hand, monovalent ions can in simulations readily occupy experimental Mg(2+) binding sites.
Keywords: Models, Molecular; simulace molekulární dynamiky; Computational Biology; RNA ribozomální; Ribosomal Proteins; RNA, Ribosomal; Molecular Dynamics Simulation; Sulfolobus acidocaldarius; molekulární modely; ribozomální proteiny; výpočetní biologie